Effect of internal iliac artery chemotherapy after transurethral resection of bladder tumor for muscle invasive bladder cancer - Li, Jianxing (Chin J Cancer Res, 2014)
OBJECTIVE: To evaluate the clinical effect of transurethral resection of bladder tumor (TUR-BT) combined with internal iliac artery chemotherapy and intravesical instillation therapy for muscle invasive bladder cancer (MIBC). METHODS: From February 2007 to April 2014, 62 patients with MIBC were treated with TUR-BT combined with intravesical instillation therapy, with or without internal iliac artery chemotherapy, and the chemotherapy regimen is gemcitabine and cisplatin (GC). The bladder preservation and survival rate as well as cancer-specific survival (CSS) rate and overall survival (OS) rate of the two groups were compared. RESULTS: Sixty-two patients were followed-up for 26-102 months with an average of 58.4±3.1 months. Recurrence-free survival (RFS) at 2-year for TUR + GC group and TUR group were 77.8% and 53.8%, respectively. Bladder preserved rate (BPR) at 3-year for TUR + GC group and TUR group were 94.4% and 80.8%. CSS rate at 2-year for TUR + GC group and TUR group were 94.4% and 84.6%. The disease-free survival (DFS) at 1-year for TUR + GC group and TUR group were 83.3% and 61.5%, and 77.8% and 53.8% for the 2(nd) year. OS at 2-year for TUR + GC group and TUR group were 88.9% and 92.3%. CONCLUSIONS: TUR-BT and intravesical instillation therapy combined with internal iliac artery chemotherapy for MIBC had a better outcome at RFS, BPR and DFS than the treatment without internal iliac artery chemotherapy, and no difference in OS and CSS.